Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?

Webimar - Adaptive Management at the Strategy Level: Portfolio Reviews and Mid Course Stocktaking - USAID (USAID, 2017)
On Wednesday, November 15, 2017 at 8:00 a.m. EST, the Bureau for Policy, Planning and Learning (PPL) held a one-hour webinar exploring Strategy-level Portfolio Reviews and Mid Course Stocktaking.

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

AdaptScan - Improving your Team's Adaptive Management - Mercy Corps (Mercy Corps, 2020)

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)